Protection from successive Omicron variants with SARS-CoV-2 vaccine and monoclonal antibodies in kidney transplant recipients - Moal, Valérie; Valade, Margaux; Boschi, Céline; Robert, Thomas; Orain, Nicolas; Bancod, Audrey; Edouard, Sophie; Colson, Philippe; La Scola, Bernard (Frontiers in Microbiology, 2023)
Kidney transplant recipients (KTRs) are at high risk of severe COVID-19, even when they are fully vaccinated. Additional booster vaccinations or passive immunization with prophylactic monoclonal antibodies are recommended to increase their protection against severe COVID-19. Here, we describe the neutralization of SARS-CoV-2 Delta, Omicron BA.1, BA.2, BA.4 and BA.5 variants, firstly by 39 serum samples from vaccinated KTRs exhibiting anti-spike antibody concentrations ≥ 264 binding antibody units (BAU)/mL and, secondly, by tixagevimab/cilgavimab. No neutralization was observed for 18% of the KTRs, while serum from only 46% of patients could neutralize the five variants. Cross-neutralization of the Delta and Omicron variants occurred for 65%–87% of sera samples. The anti-spike antibody concentration correlated with neutralization activity for all the variants. The neutralization titers against the Delta variant were higher in vaccinated KTRs who had previously presented with COVID-19, compared to those KTRs who had only been vaccinated. Breakthrough infections occurred in 39% of the KTRs after the study. Tixagevimab/cilgavimab poorly neutralizes Omicron variants, particularly BA.5, and does not neutralize BQ.1, which is currently the most prevalent strain. As a result, sera from seropositive vaccinated KTRs had poor neutralization of the successive Omicron variants. Several Omicron variants are able to escape tixagevimab/cilgavimab.